Mouthrinse recommendation for prosthodontic patients - Sheila Cavalca CORTELLI; Fernando Oliveira COSTA; Sigmar de Mello RODE; Alex Nogueira HAAS; Ana Karina Pinto de ANDRADE; Claudio Mendes PANNUTI; Elaine Cristina ESCOBAR; Eliete Rodrigues de ALMEIDA; José Roberto CORTELLI; Vinicius PEDRAZZI (Sociedade Brasileira de Pesquisa Odontológica, 2014)
Different reasons can contribute to classifying dental prosthesis wearers as high-risk individuals in relation to dental biofilm accumulation. These include a past history of oral disease, age and additional retentive areas. Other common complaints include inflammation and halitosis. Moreover, prosthesis replacement and prosthetic pillar loss are generally associated with caries and periodontal disease recurrence. Therefore, the present study undertook to make a critical review of the literature, aiming at discussing the main aspects related to chemical agent prescriptions for dental prosthesis wearers. Most of the articles were selected based on relevance, methods and availability in regard to the specific subject under investigation, without considering publication year limitations. Different types of prostheses and their impact on teeth and other oral tissues were reported. It was demonstrated that there is greater biofilm buildup and increased inflammatory levels in the presence of different types of prostheses, suggesting that additional measures are required both on population-wide and individual levels in order to control these factors. Mechanical control consists of a combination of manual or electric toothbrush and toothpaste, as well as specific devices for interdental cleaning. Although many chemical agents exhibit antimicrobial benefits when used for prosthesis disinfection, only a few agents can be used safely without causing damage. Regarding the selection of antiseptics by the overall population, chlorhexidine is the most indicated in the short term and in sporadic cases. The most indicated adjuncts to overcome the deficiencies and limitations of daily mechanical biofilm control are products containing essential oils as active ingredients.